2006
DOI: 10.1677/erc.1.01076
|View full text |Cite
|
Sign up to set email alerts
|

A molecular mimic demonstrates that phosphorylated human prolactin is a potent anti-angiogenic hormone

Abstract: S179D prolactin (PRL) is an experimentally useful mimic of naturally phosphorylated human prolactin. S179D PRL, but not unmodified PRL, was found to be anti-angiogenic in both the chorioallantoic membrane and corneal assays. Further investigation using human endothelial in vitro models showed reduced cell number, reduced tubule formation in Matrigel, and reduced migration and invasion, as a function of treatment with S179D PRL. Analysis of growth factors in human endothelial cells in response to S179D PRL show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 71 publications
2
26
0
2
Order By: Relevance
“…S179D PRL also showed physical-chemical differences, having a lower M (II)-affinity and a higher heparin-affinity. This confirms reports of PRL mutants with low Zn (II) affinity that are poorly secreted [4] and also could account for its anti-angiogenic effect [2,10].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…S179D PRL also showed physical-chemical differences, having a lower M (II)-affinity and a higher heparin-affinity. This confirms reports of PRL mutants with low Zn (II) affinity that are poorly secreted [4] and also could account for its anti-angiogenic effect [2,10].…”
Section: Resultssupporting
confidence: 91%
“…S179D prolactin (S179D PRL) is a pseudophosphorylated form of human prolactin (PRL) which has inhibitory effects on tumor growth [1] and angiogenesis [2]. The S179D PRL preparations used for these experiments consisted of properly refolded inclusion bodies (IB) from Escherichia coli [3].…”
Section: Introductionmentioning
confidence: 99%
“…The angiogenic properties of PRL vary depending upon its molecular structure. Vasoinhibins, which are proteolytic fragments of the full-length 23-kDa protein [8], and a phosphorylated 23-kDa PRL isoform [9] exert inhibitory actions on blood vessels. In contrast, several studies have shown that the unmodified 23-kDa PRL can promote angiogenesis [see review in ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, the direct effect of PRL on endothelial cells remains debatable, because most studies [6, 8, 9, 12, 15], except for one [16], failed to show any effect of PRL on the proliferation of endothelial cells in culture. Nevertheless, the PRL receptor, which belongs to the PRL-growth hormone-cytokine receptor superfamily and activates the JAK/STAT signaling pathway [17], exists in endothelial cells as short and/or long isoforms [9, 15, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…In previous experiments in multiple systems, U-PRL has been shown to promote cell proliferation (29, 49 -52) and some cell differentiation (47). Phosphorylated PRL/S179D PRL on the other hand is an antagonist to U-PRLmediated growth (4, 29, 38, 47, 49 -52), although it is one that nevertheless promotes differentiation (29,47,51) and/or apoptosis (40,41,52,53) through the generation of alternate intracellular signals (40,41,(47)(48)(49). The exact outcome of the effect of pituitary PRL therefore depends on both the total amount and the ratio of U-PRL to phosphorylated PRL released (reviewed in Ref.…”
mentioning
confidence: 97%